Visual Culture and Ideology: Analyzing Art, Media, and Public Discourse - Adriatik Basha; Klaudia Duka; Nuning Yudhi Prasetyani; Dedit Priyono (Yayasan Adra Karima Hubbi, 2026)
Background. Visual culture plays a pivotal role in shaping public discourse, influencing ideologies, and reflecting societal norms. Art, media, and other visual forms serve as critical tools for conveying messages that not only represent but also construct and reinforce dominant power structures, beliefs, and identities. As visual communication becomes increasingly pervasive in the digital age, understanding its impact on ideology is essential for unpacking how societal values are formed and contested. The objective of this study is to analyze the relationship between visual culture and ideology, focusing on how art and media shape public discourse. Purpose. This research aims to investigate how visual representations influence political, social, and cultural ideologies and contribute to the reinforcement or subversion of power structures in society. Method. A qualitative, critical discourse analysis was used to examine a range of visual media, including artworks, advertisements, social media content, and news media. The analysis focuses on identifying ideological messages embedded in visual representations and their role in shaping public understanding and opinion. Results. The study finds that visual culture plays a crucial role in shaping ideological discourse, with art and media acting as vehicles for both reinforcing and challenging dominant societal values. Key themes identified include identity construction, political power, and the commodification of social issues. Conclusion. The research concludes that visual culture is an influential force in the construction of ideology. Understanding the ideological functions of visual media provides crucial insights into how societies negotiate power, identity, and values in a visually-driven world.